Influence of Work-Family Conflict on Turnover Intention of Primary and Secondary School Teachers: Serial Mediating Role of Psychological Contract and Job Satisfaction - Li, Xiaoyu; Chen, Xinrui; Gao, Dongdong (Frontiers in Psychiatry, 2022)
Objective: Based on conservation of resource theory and social exchange theory, to explore how work-family conflict can directly and indirectly influence turnover intention, with psychological contract and job satisfaction as a mediator. Methods: A total of 505 valid data were collected on primary and secondary school teachers by using work-family conflict questionnaire, turnover intention questionnaire, psychological contract questionnaire and job satisfaction questionnaire from 3 provinces in China. Confirmatory factor analysis was used to evaluate the discriminant validity and common method bias between the four variables through AOMS, the PROCESS macro for SPSS (Model 4 and Model 6) were applied to examine the mediating effect of psychological contract and job satisfaction. Results: Work-family conflict showed a direct and positive influence on turnover intention; psychological contract was shown to play a mediating role between work-family conflict and turnover intention; job satisfaction was shown to play a mediating role between work-family conflict and turnover intention; and psychological contract and job satisfaction was shown to play a serial mediating role between work-family conflict and turnover intention. Conclusion: Work-family conflict of primary and secondary school teachers will directly lead to turnover intention. Psychological contract and job satisfaction can reduce the positive influence of work-family conflict on turnover intention. School administrators should help teachers reduce work-family conflict and take effective measures to improve psychological contract and job satisfaction, so as to reduce turnover intention.